2022
DOI: 10.1007/s00431-022-04600-x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and clinical presentation of long COVID in children: a systematic review

Abstract: A systematic literature review was conducted up to 15th February 2022 to summarize long COVID evidence and to assess prevalence and clinical presentation in children and adolescents. Articles reporting long COVID prevalence and symptoms based on original data in the paediatric population were included. Case series quality was assessed through the JBI Critical Appraisal Checklist. For observational studies, adherence to STROBE checklist was evaluated. Twenty-two articles were included: 19 observational studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
88
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(95 citation statements)
references
References 51 publications
4
88
1
2
Order By: Relevance
“…These authors did not stratify analyses by study design and pointed out the considerable risk of bias in particular because of the lack of standardised definitions of symptoms and a high level of heterogeneity [ 16 ]. Two recent systematic reviews including studies up to early 2022 reported rates of post-COVID syndrome in children ranging from 0% to 70% [ 52 , 53 ]. One of these reviews highlighted the critical risk of bias across studies, mostly due to confounding [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…These authors did not stratify analyses by study design and pointed out the considerable risk of bias in particular because of the lack of standardised definitions of symptoms and a high level of heterogeneity [ 16 ]. Two recent systematic reviews including studies up to early 2022 reported rates of post-COVID syndrome in children ranging from 0% to 70% [ 52 , 53 ]. One of these reviews highlighted the critical risk of bias across studies, mostly due to confounding [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…When compared with adults, PASC in children may present with a milder clinical course 21 , leading to underdiagnosis in the health care setting. Some effects of PASC may have been seen in school performance or extracurricular participation, neither of which may have been captured in the HER.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, long COVID in children is an emerging concern [ 10 ]. There is a pressing need for studies to look at this outcome as well.…”
mentioning
confidence: 99%